PENERAPAN SISTEM GOOD MANUFACTURING PRACTICES (GMP) PADA PROSES PEMBEKUAN IKAN ANGGOLI (Pristipomoides multidens) - Juhariyah Juhariyah; Ika Junianingsih (Samakia : Jurnal Ilmu Perikanan, 2014)
The purpose of this study is to find out directly about the application of the system of Good Manufacturing Practice (GMP) on the freezing fish anggoli CV. Jay Bee Seafoods Village Mayangan Probolinggo, East Java in January to April 2014. The method used in this research is a survey method, the technique of primary data collection is done through observation, interviews, documentation and direct participation in the field. Secondary data was collected through literature. Good Manufacturing Practice (GMP) is a guideline how to produce food in order for manufacturers to meet the requirements that have been determined to produce quality food products according to the demands of consumers. Implementation of good manufacturing management system starting from raw material control process until the delivery of the product to consumers. Stages of freezing fish activity Anggoli (Pristipomoides multidens) CV. Jay Bee Seafoods include Raw Material Procurement, Weighing I, Weighing II, Shelter, Filleting, Fish Duri revocation, Skin Lest, Triming, washing, wrapping and preparation, Freezing, metal detection / metaldetector, Packing, Storage, Distribution and Marketing. In general, the process of freezing the fish anggoli held in CV. Jay Bee seafoods have implemented the GMP system